Potensi Dan Pengembangan Obyek Pariwisata Curug Jeglong Kabupaten Kendal Kabupaten Plantungan Jawa Tengah - M Fathurrahman Nurul Hakim (STIE Pariwisata API Yogyakarta, 2019)
This study examines the Potential and Tourism Development of Jeglong Waterfall, Paltungan District, Kendal Regency, Central Java. This study aims to determine the potential and strategy of Jeglong Curug Tourism development that is owned, as well as the problems faced in developing Jeglong Curug Tourism in Kendal. This research is presented descriptively describing information about attractions. Data collection methods proposed in this study were interviews, observation and literature studies. In this study the author discusses the following variables: 1. Potential and attractiveness possessed by Jeglong Waterfall 2. Development strategies applied by the residents of Plantungan to the Jeglong Curug tourist attraction. The results of this study indicate that: Jeglong Waterfall Tourism Object is one of the potential tourism objects to be developed in Kendal Regency. In the development of Jeglong Curug Tourism Object, it turns out that there are still various obstacles, including: The lack of supporting facilities for Jeglong Curug Tourism Object, and the limited Human Resources and funds used for development. So it can be concluded that Jeglong Waterfall Tourism Object turned out to have potential as an attractive natural tourist attraction to be developed. The participation of the government / community and academics in the field of Tourism is very much needed, so that it can increase the number of tourists so that it can increase the economic income of the community and promote tourism especially in Plantungan District, Kendal Regency.